Limit theorems for systems of the type M θ/G/1/b with resume level of input stream - Bratiychuk, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
A finite capacity queueing system of the type M θ/G/1/b is considered in which the input flow is regulated by some threshold level. Asymptotic properties of the first busy period and the number of customers served for this period are studied.